A novel measurement method for accurate heat accounting in historical buildings. (September 2020) - Dell'Isola, M.; Ficco, G.; Di Pietra, B.; Saba, F.; Masoero, M.C.
Highlights: Heat accounting is an essential tool for increasing energy efficiency of buildings. Indirect accounting systems are widely used in existing buildings generally showing not high accuracy. A new hybrid method has been developed aimed at improving accuracy of heat accounting. The hybrid method has been experimented at INRIM, the Italian metrology institute. The hybrid method always shows higher accuracy in respect to the indirect one. Abstract: Nowadays, two different heat accounting methods are available: the direct method, based on heat meters, and the indirect one, based on heat cost allocators. Unfortunately, in existing buildings, due to the plant configuration, heat meters are often technically unfeasible or not cost efficient, whereas heat cost allocators can be easily installed in almost all conditions. At the same time, the indirect method relies on a high number of interconnected devices with installation and operative conditions often variable within the same building and influencing the on-field metrological performances. In this paper, the authors propose a novel "hybrid" method for accurate heat accounting combining the advantages of indirect method with the higher accuracy typical of direct methods. The proposed method has been experimented at INRIM, the primary metrology institute in Italy, assessing the on-field performance in a virtual eight-apartments building. The experimental results show that the proposed method always presents improved accuracy.